Local Wisdom and Santri Culture Integration in Character Formation: Integrasi Kearifan Lokal dan Budaya Santri dalam Pembentukan Karakter - Hamidah, Dina Briliana; Shoimah, Retno Nuzilatus; Winnuly, Winnuly (Academia Open, 2026)
General Background: Education plays a strategic role in shaping human resources not only cognitively but also in developing character and ethics from an early age. Specific Background: The advancement of globalization and technology has led to moral value shifts, while character education in elementary schools remains less contextual, particularly within Islamic educational settings. Knowledge Gap: Studies focusing on the integration of local wisdom through santri culture in Islamic elementary schools within pesantren environments are still limited. Aims: This study aims to analyze the implementation of local wisdom-based education through santri culture in shaping students’ character and ethics at SDI Tanwirul Qulub. Results: Using a qualitative case study approach with observation, in-depth interviews, and documentation, the findings show that the integration is implemented through habituation, exemplary behavior, and hidden curriculum, where santri culture as religious local wisdom fosters respectful attitudes, discipline in worship, social ethics, and student confidence. Novelty: This study offers an integrative model of character education based on local wisdom by positioning santri culture as a form of religious local wisdom internalized through daily practices in a pesantren-based elementary school context. Implications: The findings provide a conceptual and practical alternative for strengthening character education in Islamic elementary schools through the integration of formal learning and pesantren cultural values. Highlights• Integration of school curriculum with pesantren traditions shapes moral development• Daily habituation and role modeling build discipline, respect, and social ethics• Collaborative roles of teachers and caregivers sustain value internalization KeywordsLocal Wisdom Education; Santri Culture; Character Formation; Ethics Education; Islamic Elementary School